Effectiveness of Parent Focused Group Program on ObesityRelated Behavior & Anthropometric Measurements among 6-12-Year-old Obese Children-A Pilot Study (Medico Legal Update, 2021)
Background: Obesity is caused due to the mismatch between energy intake and expenditure, with foodintake more than the requirements leading to an increase in Body mass index (BMI) as a body measurementparameter1. Parent focused group program is an intervention program where parents are involved in targetingthe changes in obesity-related behavior of their obese children.Objectives: To determine the effectiveness of parent-focused group programs on obesity-related behaviorsof children aged 6-12 years.Method and Results: The study was conducted in two phases. The first phase included a survey design toidentify overweight and obese children from two randomly selected schools as control and experimentalfromthe southern part of Kerala, India. The second phase includedan intervention design with a parent-focusedgroup program for the program’s experimental group, and effectiveness was analyzed from children’sobesity-related behaviors. The key findings indicated that the parent-focused group program was effectivein the pre-test and post-test scores of anthropometric measures in the experimental group for both boysand girls. The study suggested that parent-focused programs effectively bring changesin children’s obesityrelated behavior, thus reducing the chances of getting overweight/obese.Conclusion: Parent-focused group interventions are effective as a preventive strategy in reducing obesityrelated behavior among children.